2020
DOI: 10.1002/jmv.26278
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal coinfection in COVID‐19 patients

Abstract: We would like to report our experience of 2 patients co‐infected with Streptococcus pneumoniae (S. pneumoniae) and coronavirus disease 2019 (Covid‐19) in the United Kingdom. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…Elevated markers of liver injury, high C-reactive protein, and low lymphocytes at admission were associated with adverse outcomes in Chinese patients with COVID-19 ( 28 , 29 ), but we found no significant changes of the abovementioned parameters possibly associated with medication concealing. The occurrence and the cumulative value of identified co-infections during hospitalization were positively associated with longer ICU stay in both survivors and non-survivors, and this may be linked with the disruption of host defenses that are no longer able to prevent pathogen migrations ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated markers of liver injury, high C-reactive protein, and low lymphocytes at admission were associated with adverse outcomes in Chinese patients with COVID-19 ( 28 , 29 ), but we found no significant changes of the abovementioned parameters possibly associated with medication concealing. The occurrence and the cumulative value of identified co-infections during hospitalization were positively associated with longer ICU stay in both survivors and non-survivors, and this may be linked with the disruption of host defenses that are no longer able to prevent pathogen migrations ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common bacteria were M. pneumonia , P. aeruginosa, and Haemophilus influenza . Toombs et al [ 21 ] found that two COVID-19 patients (0.4%) were co-infected with S. pneumoniae , as determined by blood culture positivity upon hospitalization in the United Kingdom. These results support the hypothesis of secondary infection in COVID 19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians are challenged with the additional burden of possible coinfections with other tropical diseases that have the potential to complicate the course of illness [26]. Coinfections with COVID-19 have been reported with multiple bacteria and viruses [27][28][29][30][31]. Nevertheless, coinfection with dengue viruses and SARS-CoV-2 are still scarce, with only a few reports describing false-positive dengue serology [24,32].…”
Section: Discussionmentioning
confidence: 99%